Estudio del incumplimiento de las declaraciones del Impuesto al Valor Agregado y su incidencia en el nivel de multas aplicadas a la empresa Piladora Mia - Portilla Ayala, Valentina Isabel (2021)
Tax collection is an act carried out by the state, and its objective is to gather all that capital to invest it and use it in different spaces, be they administrative, health, education, etc., so that this is possible, the obligations that the Taxpayers must comply, but unfortunately these obligations are not carried out on time by taxpayers. The investigation carried out in Piladora Mia, whose legal representative is Olivo Ayala Verónica Rocío is a Natural Person type taxpayer with RUC 1204554412001, was established by Mrs. Olivo on April 7, 2004. She is required to keep accounting and was established as an agent retention. Its main economic activity is Wholesale of Cereals (Grains) and seeds. It currently has two establishments, one in the city of Ventanas and the other in the city of Guayaquil. This work focused on the establishment of the city of Ventanas. At present, tax collection has improved in the country, and the Internal Revenue Service carries out controls so that natural and legal persons comply with their tax obligations and thus avoid paying incense fines. The Value Added Tax is a very important source of income for the country, since all the goods that are sold and the services that are provided are taxed with this tax.